Use of oral probiotics in inflammatory skin diseases. Literature review - Laura Prado Franco de Godoy; Flavia Garcia Michalichen; Raul Cartagena Rossi; Sabrina Bortoletto Gomes de Aquino; Flávia R. Ferreira (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
The gut microbiome is an important in the health and pathogenesis of some diseases. Beyond digestion, it interferes with the immune system and even with the skin health. Evidence shows that intestinal changes can be involved in dermatological manifestations, such as rosacea, acne, and atopic dermatitis. The use of probiotics has been studied, because it is possible to create a strategy to modulate the immune system and reduce the manifestations of these diseases. In this study, we performed a bibliographic review of the clinical evidence on the use of oral probiotics in the treatment of rosacea, acne, and atopic dermatitis. The search was made in electronic databases, such as PubMed, Scientific Electronic Library Online (SCIELO), Latin American Literature in Health Sciences (LILACS), and Google Scholar, in the past 5 years. A limited number of studies have been found, but all have shown the benefit and improvement of lesions in patients, as well as the reduction of pro-inflammatory cytokines by the mechanism of immunomodulation. Search results found out that the use of Lactobacillus acidophilus, Bifidobacterium lactis, and Bifidobacterium bifidum are promising in the three pathologies. Moreover, probiotics used in association with oral antibiotics obtained better responses than when used alone. Despite the positive response, more efforts are required to fully understand the exact mechanisms and therapeutic effects of probiotics in the management of inflammatory dermatological diseases.